2021
DOI: 10.1038/s41598-021-93912-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for urosepsis in chronic kidney disease patients with urinary tract infections

Abstract: Occurrence of urosepsis is not uncommon following urinary tract infections (UTI). However, there is a lack of evidence explaining the risk factors predisposing to urosepsis in patients with chronic kidney disease (CKD). This retrospective study was undertaken to evaluate the incidence and possible risk factors for urosepsis among patients hospitalized with UTI in a cohort of CKD patients. Patients were divided into the urosepsis group and the non-urosepsis group. Of 489 hospitalized patients with UTI, 70 (14.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Proteus mirabilis which is a causative agent of cystitis and pyelonephritis primarily in individuals with indwelling catheters or structural abnormalities and K. penumoniae is frequently opportunistic pathogens implicated in UT and catheter associated UTIs of hospitalized patients it has been suggested to involve the formation of biofilms on this surface include adherence factors. Each of Proteus mirabilis and K. penumoniae are pathogens implicated in catheter associated UTI and had been isolated from urosepsis patients in the present study, in study of Jessica reported same frequencies of Proteus mirabilis [32] and Dimitrijevic et al reported 11.7% of K. penumoniae causes urosepsis while in this study finding showed 7.7% [33].…”
Section: Discussionsupporting
confidence: 65%
“…Proteus mirabilis which is a causative agent of cystitis and pyelonephritis primarily in individuals with indwelling catheters or structural abnormalities and K. penumoniae is frequently opportunistic pathogens implicated in UT and catheter associated UTIs of hospitalized patients it has been suggested to involve the formation of biofilms on this surface include adherence factors. Each of Proteus mirabilis and K. penumoniae are pathogens implicated in catheter associated UTI and had been isolated from urosepsis patients in the present study, in study of Jessica reported same frequencies of Proteus mirabilis [32] and Dimitrijevic et al reported 11.7% of K. penumoniae causes urosepsis while in this study finding showed 7.7% [33].…”
Section: Discussionsupporting
confidence: 65%
“…Regarding non-infectious complications in hospitalized patients with UTIs, namely AKI, in a European cohort of 489 CKD patients, the reported rate of AKI in patients hospitalized for UTIs was 73.6%, the mean length of hospital-stay (days) 13.2 ± 18.5 [ 26 ] compared to a 34.9% incidence of AKI and 8.33 ± 5.82 days mean length of stay in our group. Other studies reported AKI incidence in hospitalized patients ranging from 45.4% [ 10 ] to 75.2% in a kidney transplant cohort [ 39 ].…”
Section: Discussionmentioning
confidence: 78%
“…It is known that the CKD population has an increased susceptibility to infectious events, both community-acquired and hospital-acquired [ 3 , 4 , 23 , 24 ]. This could be explained in part by frequent contact with the healthcare system, higher comorbidity index, impaired host defense mechanisms secondary to immune system impairments in both humoral and cellular immune responses, cytokine generation and oxidative stress [ 3 , 25 , 26 , 27 , 28 ]. Specifically, for increased susceptibility to UTIs, some of the potential risk factors are urinary tract abnormalities, disruption of the urinary epithelial barrier or impaired regeneration capacity, impaired bladder voiding, impairment in inflammasome signaling [ 29 ], progressive loss of kidney functions associated to decreased levels of urinary secreted molecules, namely antimicrobial peptides such as β-defensin 1, urinary uromodulin–a multifunctional protein also implicated in susceptibility and immune response to UTI [ 30 , 31 ] and other urothelium-secreted antimicrobial substances, such as tissue-type plasminogen activator and urokinase-type plasminogen activator [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term urinary catheter users often have multiple medical, surgical, and even radiotherapeutic background, following damage to the detrusor muscle's structure, and consequent bladder alteration emptying, recurrent UTI, and high prevalence of renal scarring, caliectasis, and CKD (33). These antecedents associated with the permanent presence of a catheter increase the risk of suffering urosepsis (34).…”
Section: Discussionmentioning
confidence: 99%